Microfluidic-Based Platform for the Evaluation of Nanomaterial-Mediated Drug Delivery: From High-Throughput Screening to Dynamic Monitoring - Yang, Yamin; Liu, Sijia; Geng, Jinfa (Current Pharmaceutical Design, 2019)
Nanomaterial-based drug delivery holds tremendous promise for improving targeting capacity, biodistribution, and performance of therapeutic/diagnostic agents. Accelerating the clinical translation of current nanomedicine requires an in-depth understanding of the mechanism underlying the dynamic interaction between nanomaterials and cells in a physiological/pathophysiological-relevant condition. The introduction of the advanced microfluidic platform with miniaturized, well-controlled, and high-throughput features opens new investigation and application opportunities for nanomedicine evaluation. This review highlights the current state-of-theart in the field of 1) microfluidic-assisted in vitro assays that are capable of providing physiological-relevant flow conditions and performing high-throughput drug screening, 2) advanced organ-on-a-chip technology with the combination of microfabrication and tissue engineering techniques for mimicking microenvironment and better predicting in vivo response of nanomedicine, and 3) the integration of microdevice with various detection techniques that can monitor cell-nanoparticle interaction with high spatiotemporal resolution. Future perspectives regarding optimized on-chip disease modeling and personalized nanomedicine screening are discussed towards further expanding the utilization of the microfluidic-based platform in assessing the biological behavior of nanomaterials.
Keywords: drug delivery